Fur microbiome as a putative source of symbiotic bacteria in sucking lice - Martin Říhová, Jana; Gupta, Shruti; Nováková, Eva; Hypša, Václav (Scientific reports, 2024)
Symbiosis between insects and bacteria has been established countless times. While it is well known that the symbionts originated from a variety of different bacterial taxa, it is usually difficult to determine their environmental source and a route of their acquisition by the host. In this study, we address this question using a model of Neisseriaceae symbionts in rodent lice. These bacteria established their symbiosis independently with different louse taxa (Polyplax, Hoplopleura, Neohaematopinus), most likely from the same environmental source. We first applied amplicon analysis to screen for candidate source bacterium in the louse environment. Since lice are permanent ectoparasites, often specific to the particular host, we screened various microbiomes associated with three rodent species (Microtus arvalis, Clethrionomys glareolus, and Apodemus flavicollis). The analyzed samples included fur, skin, spleen, and other ectoparasites sampled from these rodents. The fur microbiome data revealed a Neisseriaceae bacterium, closely related to the known louse symbionts. The draft genomes of the environmental Neisseriaceae, assembled from all three rodent hosts, converged to a remarkably small size of approximately 1.4 Mbp, being even smaller than the genomes of the related symbionts. Our results suggest that the rodent fur microbiome can serve as a source for independent establishment of bacterial symbiosis in associated louse species. We further propose a hypothetical scenario of the genome evolution during the transition of a free-living bacterium to the member of the rodent fur-associated microbiome and subsequently to the facultative and obligate louse symbionts.
Keywords: Animals; RNA, Ribosomal, 16S; Sucking lice; Phylogeny; Anoplura; mikrobiota; Fur microbiome; symbióza; zvířata; Microbiota; fylogeneze; Symbiosis; Metagenomics; Bacteria; Rodents; RNA ribozomální 16S; Phthiraptera